A review of China's road traffic carbon emissions. (10th January 2019) - Zhang, Linling; Long, Ruyin; Chen, Hong; Geng, Jichao
Abstract: Road traffic is one of the main sources of carbon emissions that cause climate change. Despite numerous studies on road traffic emissions, significant challenges remain in carbon emissions measurement and quantitative evaluation of mitigation effects. This paper first reviews the measurement of carbon emission from road traffic including the top-down model and the bottom-up model. Then, we summarize the main factors that affect the traffic carbon emissions, which are divided into three categories: demand side factors, supply side factors and environmental measurement factors. Finally, traffic mitigation measures from economic, technical and administrative aspects are examined. Based on the review, we can conclude that the results of carbon emissions calculated by different methods are quite different, and there are differences in the accuracy and application scope of various methods. Each type of factor plays a different role in the process of traffic reduction, in which the demand factors are the roots, the supply factors are the means, and the environmental factors are the conditions. The development of traffic mitigation measures is not targeted, and there is a lack of quantitative research on policy effects. In the future, it is necessary to standardize the statistical caliber and error standard of measurement of carbon emission for road traffic, and to clarify the responsibility of emission reduction from various traffic subjects. More research efforts need to be focused on quantifying the effect of mitigation measures.